Evaluasi dan Perbaikan Proses Bisnis Menggunakan Business Process Improvement (BPI) (Studi Kasus: Bidang Komunikasi, Dinas Komunikasi dan Informatika Kota Batu) - Theresia Emiliana Boleng; Nanang Yudi Setiawan; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika has main business processes in the Communication Field that consist of business processes for forming community information groups, fostering community information groups, gathering news, reporting and publishing news, and maintaining KIM web. In the daily implementation of the business process, there are several problems that interfere with the business process. There are 6 problems found in the implementation, which are several mistakes in spreading the invitation letter, misunderstandings among stakeholders, not conducting data mining, collecting invalid information, report manipulation due to the delay in collecting KIM reports and making solutions that were not in accordance with the target. Based on existing problems, it is necessary to evaluate business processes and make improvements to business processes. The first step is to conduct analysis and evaluation using the Failure Mode and Effect Analysis (FMEA) method so it can analyze the problem deeply and sort the problem based on the highest RPN value that will be used as an evaluation. In determining ranking, it is assisted by the role of stakeholders in it. Continued to stage of preparing recommendations for business process improvement using the Business Process Improvement (BPI) method with the help of tools at BPI, named streamlining. From the simulation results of current business processes (as is) and recommendations (to be) on business processes reporting and publishing news, it was found that an increase in time analysis experienced an increase in time effectiveness of up to 54.34%. The conclusion from the result is the business process recommendations (to be) can produce a faster duration of problem-solving and produce recommendations that can be applied to minimize problems that occur based on the results of analysis and evaluation.